Populism and Social Policy in Transitional Societies: Strategies and Impact on Marginalized Groups in Central and Eastern Europe and Latin America - Gajić, Draško (Ревија за социјална политика/Journal of Social Policy, 2024)
Countries in Central and Eastern Europe and Latin America that have undergone significant political and economic changes face new challenges in shaping social policy. Populist leaders in these regions often use social policy as a tool for gaining political support, targeting marginalized groups as part of their strategies. This paper analyzes various approaches of populist regimes in transitional societies and their impact on social policy, particularly toward marginalized groups. Through case studies from Hungary, Poland, Serbia, Turkey, Venezuela, and Brazil, the paper offers a comparative overview of populist strategies. The analysis includes a systematic literature review and a comparative analysis of empirical examples of social policy under populist regimes, incorporating a theoretical framework based on the concept of “welfare nationalism” and specific case studies. Findings reveal that populist leaders use social policy to strengthen political control and support, with varying approaches to marginalized groups depending on regional and cultural contexts. Transitional societies represent fertile ground for populist strategies that use social policy as a tool for political mobilization. This research highlights the need for more inclusive social policies to mitigate the adverse effects of populism.
Keywords: populism; social policy; transitional societies; marginalized groups; comparative analysis